Effect of hematoma volume on the 30-day mortality rate of patients with primary hypertensive brainstem hemorrhage: a retrospective cohort study - Yu, Zhenxing; Zhang, Xianbin; Xu, Qiming; Zhang, Zhipeng; Xia, Yu; Li, Huaquan; Yu, Xiang; Deng, Lei; Zhang, Long (Frontiers in Surgery, 2023)
Abstract Objective: The purpose of this study is to investigate the effect of hematoma volume on the 30-Day Mortality Rate of patients with Primary Hypertensive Brainstem Hemorrhage (PHBH). Methods: Retrospective analysis was done on the clinical information of 74 patients who underwent treatment for primary hypertensive brainstem hemorrhage at the Department of Neurosurgery of the 908th Hospital of the Joint Logistic Support Force of the Chinese People's Liberation Army between January 2018 and December 2021. Both univariate and multivariate logistic regression were used to assess clinical signs and risk factors that affect 30-day mortality. Result(s): In the 74 patients with primary hypertensive brainstem hemorrhage included in this investigation, 46 patients died and 28 patients survived. The mortality rate at 30 days was 62.16%. A statistically significant difference was seen (P < 0.001) in the results of the univariate analysis, which suggested that hematoma volume may be a factor affecting the prognosis of patients with hypertensive brainstem hemorrhage. Hematoma volume was further demonstrated to be a risk factor and an independent factor impacting death in patients with brainstem hemorrhage (P<0.001) by multivariate logistic regression analysis (OR: 2.6, 95% CI: 1.7-3.9, P<0.001 Crude Model, OR: 3.6, 95% CI: 1.7-7.7, P<0.001 Multivariate-Adjusted Model). After adjusting for confounding variables, the hematoma volume was revealed to be an independent predictor of 30-day death in patients with brainstem hemorrhage. We discovered by smooth curve fitting that hematoma volume increased in a non-linear manner with 30-day mortality. The 30-day mortality rate did not alter significantly when the hematoma volume was less than 4 ml. When the hematoma volume was greater than 4ml, the 30-day mortality rate increased rapidly, and when the hematoma volume was 10ml, the 30-day mortality rate reached the maximum. Conclusion(s): Hematoma volume is an independent factor affecting 30-day mortality in patients with primary hypertensive brainstem hemorrhage. The severe and extensive neurological damage caused by primary hypertensive brainstem hemorrhage is highly unlikely to be fundamentally altered by a single protocol, and new avenues need to be explored scientifically and continuously.